2019
DOI: 10.1039/c9na00493a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochromic carbon dots as smart sensors for water sensing in organic solvents

Abstract: The present study highlights the potential of using hydrochromic carbon dots as probes for sensing water contamination in organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…Carbon dots were prepared by carbonization of brown sugar. A detailed characterization has been published previously by our group [34]: their diameter was measured to be ca. 4.12 ± 0.54 nm and their emission spectrum was centered at 448 nm under an excitation of 300 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon dots were prepared by carbonization of brown sugar. A detailed characterization has been published previously by our group [34]: their diameter was measured to be ca. 4.12 ± 0.54 nm and their emission spectrum was centered at 448 nm under an excitation of 300 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon dots were prepared following the procedure described in our previous work [34]. In short, equal amounts of brown sugar and water were heated in a furnace at 180 • C (5 • C/min) for 48 h, resulting in carbonization.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…The CDs exhibited red shift in the presence of water in aprotic solvents, whereas, in protic solvents, the emission intensity was increased. Therefore, this property of the CD was employed to probe water contamination in different solvents [ 133 ]. Different solvents have different emission wavelengths.…”
Section: Cds As Smart Materialsmentioning
confidence: 99%
“…The kinetics studies revealed slow release of SDZ and also exhibited good inhibitory effects against Escherichia coli and Staphylococcus aureus. The biocompatible nature is a most important parameter for the materials intended for biological applications and their toxicity nature in any possible exposure state should be evaluated for their successful applications [73][74][75][76][77][78]. Therefore, the biocompatible studies conducted on the PLA nanofibers containing SDZ and [Mg-Al]-LDH has shown good biocompatible nature in the human HDFn cells.…”
Section: Synthetic Polymeric Nanofibers Based Wound Dressingsmentioning
confidence: 99%